Evolution of documents related to performance in boccia: a paralympic sport bibliometric analysis - Cátia C. Ferreira; Cátia C. Ferreira; Cátia C. Ferreira; Víctor Hernández-Beltrán; José M. Gamonales; José M. Gamonales; Mário C. Espada; Mário C. Espada; Mário C. Espada; Mário C. Espada; Mário C. Espada; Jesús Muñoz-Jiménez (Frontiers in Sports and Active Living)
BackgroundThe purpose of this study was to develop a bibliometric review of literature related to Boccia, aiming to analyse relevant information related to the adapted sport, and determine the existing relationships/networks between the different authors and countries, as well as methodological procedures of publications.MethodsThe Web of Science database was used, considering the keywords “Boccia” OR “Bocha” AND “Sport”, applying the filter “topic” to identify documents containing this term in the title, abstract, or keywords. A total of 89 studies were found and 38 selected based on the criteria, published until November 2024.ResultsFrom 2012 forward, the number of studies increased by 81.87% from 2017 to 2024, with a notable rise between 2017 and 2020. Two documents had 20 or more citations, and a total of 119 authors were associated with 38 selected documents, an average of 3.6 authors per document. Portugal and Spain present the highest number of documents (n = 9), but Spain has more than twice thecitations compared to Portugal (58 vs.17). From a total of 29 resources, Springer Nature had the highest number of studies indexed in its platforms (n = 7). A total of 92 keywords were identified, and the terms with the highest occurrence were “boccia” (n = 17), “rehabilitation” (n = 4), and “disability” (n = 4). Brazil and Indonesia were the countries with the most recent scientific production, and 90.6% of the studies were written in English and 9.4% in Spanish.ConclusionsThe findings emphasize the limited research output in Boccia, particularly regarding performance analysis, coaching methodologies, and athlete development. Future studies should explore training strategies, physiological demands, and the impact of Boccia on athleteś development and social inclusion.